Prototype Mesin ATM Beras Menggunakan E-KTP Berbasis Arduino - Indah Suci Ramadani; Ade Zulkarnain Hasibuan; Kalvin Chiuloto (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
The Raskin program is a program from the government to reduce the burden of spending on the Indonesian people. With existing technological facilities, distribution problems for the Raskin program can be reduced. Rice distribution is an activity that is often carried out around the community. However, rice distribution often takes a very long time and causes long and inefficient queues. To overcome this, an Arduino-based Rice ATM was created to facilitate the distribution of rice using an Arduino microcontroller, photoelectric sensor, loadcell, Rfid, and rice distribution servo motor. can identify objects that have been marked with a unique identifier code. Based on this, this study discusses the rice ATM system using an Arduino-based e-ID card. The results of the testing and implementation of this system are that when the RFID card is tapped, then the ID and balance are checked on the oled lcd, if appropriate, the servo motor will open and remove the rice and if the RFID tag used is not appropriate and the balance provided has run out, the servo motor will not work. open. Distance and position of RFID reading after 1 test. Picking up rice at this ATM is only done 1 time 1 day in 1 card, if you want to take more than 1 time the e-KTP must be reset, the quantity issued by this rice atm system is 1 kg. From these problems, an ATM Rice tool was produced using a weight sensor or loadcell. From the results of testing this tool works well and is able to overcome the problems that have been experienced by the community